Effects of Dexmedetomidine on Emergence Agitation and Recovery Quality Among Children Undergoing Surgery Under General Anesthesia: A Meta-Analysis of Randomized Controlled Trials - Yang, Xiaoli; Hu, Zhenyu; Peng, Fei; Chen, Guangxiang; Zhou, Yu; Yang, Qiange; Yang, Xiaoling; Wang, Maohua (Frontiers in Pediatrics, 2020)
Background: Emergence agitation is one of the most common and intractable postoperative complications among children undergoing surgery with general anesthesia. Our aim was to evaluate the efficacy of dexmedetomidine for preventing emergence agitation in children after general anesthesia. Methods: PubMed, Cochrane Library, EMBASE and Web of Science databases were comprehensively searched for all randomized controlled trials published before April 22th, 2020 that investigated the efficacy of dexmedetomidine for prevention of emergence agitation in children after general anesthesia. Meta-analysis was performed with Review Manager 5.3. Our primary outcome was the incidence of emergence agitation. Second outcomes included: number of patients need rescue analgesic, number of patients having postoperative nausea and vomiting, emergence time, extubation time, time to discharge from post-anesthesia care unit. Results: Thirty-three studies involving 2549 patients were included in our meta-analysis. Compared to placebo, dexmedetomidine significantly reduced the incidence of emergence agitation [risk ratio (RR) 0.29, 95% confidence interval (CI) 0.22-0.37, P<0.00001]. Dexmedetomidine also reduced the incidence of postoperative nausea and vomiting [risk ratio (RR) 0.46, 95% confidence interval (CI) 0.3-0.69, P=0.0002] and the requirement of rescue analgesic [risk ratio (RR) 0.29, 95% confidence interval (CI) 0.18-0.44, P<0.00001]. While, patients in the dexmedetomidine group experienced a longer emergence time [risk ratio (RR) 2.18, 95% confidence interval (CI) 0.81-3.56, P=0.002]and a longer extubation time [risk ratio (RR) 0.77, 95% confidence interval (CI) 0.22-1.31, P=0.006]. There was no significant difference in terms of time to discharge from post-anesthesia care unit [risk ratio (RR) 2.22, 95% confidence interval (CI) -2.29-6.74, P=0.33]. When compared to midazolam, propofol, fentanyl, tramadol, clonidine and other drugs, no significant difference was found for the incidence of emergence agitation and other comparisons except for the requirement of rescue analgesic [risk ratio (RR) 0.45, 95% confidence interval (CI) 0.33-0.61, P<0.00001]. Conclusions: Dexmedetomidine has a positive effect on prevention of emergence agitation, relieving postoperative pain, reducing the consumption of rescue analgesic and the incidence of postoperative nausea and vomiting.